Recruitment of Arabic calligraphy in gold jewelry styles (Al-Academy, 2016)
Search came (the employment of Arabic calligraphy in gold jewelry styles) four chapters, the first chapter of which dealt:A/research problem B/importance of research C/targets search D/ Define termsAs the aim of the research (to identify the employment of different forms of Arabic calligraphy on gold jewelry styles).It came in the second quarter (the theoretical framework and previous studies), some of the topics reviewed in which diversities researcher aesthetic and functional, and various uses that filled Arabic calligraphy.The third chapter outlining the researcher methodology and the research community, has a special form for the analysis of the samples are designed as form is offered on a number of experts in the field of jurisdiction to indicate suitability for the application, as identified where some underpinnings own analysis, after discussion with experts and display the vocabulary they proved their applicability , so the researcher on the basis of analysis of research samples, which amounted to (6) samples.In the fourth quarter proved the most important researcher's findings through the theoretical framework and previous studies and analysis of the samples, also came when some conclusions and proposals, and finally singled researcher list of sources used in the search